Qualitative Study on Clinico-Social Problems of Brick-Kiln Workers: A Study from Anand, Gujarat - Deepak Kumar Sharma; Arun Varun; Mansi Patel (Medsci Publications, 2013)
Background: The brick kilns serve as a source of livelihood for thousands of unskilled laborers from across the country. The seasonal nature of the work attracts migrant labour, many of them landless farmers. Objectives: The study was done with a view to know the clinico-social problems of the families. Materials and methods: The following study is a focused group discussion with brick kiln workers in the catchment area of RHTC of Pramukhswami Medical College. Results: In the current study it was found that the condition of these migrant brick kiln workers is very pathetic on account of number of conditions. All the workers were migrant and marginal workers with migration duration of 8 months every year and then they are going back to the native place. These workers were mostly illiterate or had primary education. Females were uneducated. These workers are getting daily wages and there is no holiday as such. The days these workers don't work are non-paid days. Almost all these workers complained of bodily pains. Children in these families are usually suffering from respiratory tract infections, diarrhea and intestinal infections. Conclusions: Irrespective of the migration status, local governance should do something for their benefit and health so that some decent work can be ensured.